Специфика функционирования знаковых американских реалий в системе языка и речи - Жукова, Л.К.; Стрембицкая, Н.С. (Культура народов Причерноморья, 2002)
The article is devoted to the problem of functioning of American political realia “liberty” and “freedom” in the process of place names’ nomination. Being one of the main values of American nation and basis of American national consciousness, they are widely used in the system of toponymic nomination, conveying the main features and peculiarities of the American society. Functioning independently as well as parts of compound place names, these realia build up word combinations according to different models (N+N, Adj.+N, etc.), which were also analyzed in the article.